(untitled) (Medical Forum Monthly, 2020)
Objective: Central neuraxial blocks have been mainstay for elective caesarian sections. Epidural anesthesia is better tolerated haemodynamically and provides titer able analgesia and prolonged duration of analgesia. Shivering in perioperative period is reported as high as 65% in general anesthesia and 33% in central neuraxial anesthesia. Intravenous tramadol has been used for decades to treat perioperative shivering. Epidural tramadol as adjuvant to local anesthesia increases quality and duration of anesthesia. We aimed to note efficacy of epidural tramadol. Study Design: Prospective, Randomized Control Trial study. Place and Duration of Study: This study was conducted at the Operation theatres of Sahara Medical College, Narowal from January, 2020 to July, 2020. Materials and Methods: Total number of 250 patients included in study randomly divided in group 1 and 2, received epidural and intravenous tramadol consecutively. SPSS software was used to analyze statistics. Results: Group 1 resulted in 7 patients with shivering mean time to shivering was 41.42+7.29 minutes and mean APGAR was 7.56+1.14,9.83+0.41,9.99+0.08 at 1,5 and 10 minutes consecutively. Group 2 resulted in 6 patients with shivering mean time to shivering was 43.66+4.27 minutes and mean APGAR was 8.48+0.85, 9.78+0.62,9.97+0.15 at 1,5 and 10 minutes consecutively. Shivering and time to shivering between 2 groups were insignificant with significance level of p=0.777 and p=0.524 consecutively. APGAR at 1 minute was significant with level of p< 0.001 whereas at 5 and 10 minutes improved and became insignificant with p=0.478 and p=0.315 levels consecutively. Nausea vomiting was insignificant between 2 groups p=0.856. Conclusion: Epidural tramadol is as effective as intravenous tramadol for perioperative shivering.